The O-fucosyltransferase O-fut1 is an extracellular component that is essential for the constitutive endocytic trafficking of Notch in Drosophila. - Sasamura, T.; Ishikawa, H.O.; Sasaki, N.; Higashi, S.; Kanai, M.; Nakao, S.; Ayukawa, T.; Aigaki, T.; Noda, K.; Miyoshi, E.; Taniguchi, N.; Matsuno, K. (Development, 2007)
Notch is a transmembrane receptor that mediates the cell-cell interactions necessary for many cell-fate decisions. Endocytic trafficking of Notch plays important roles in the activation and downregulation of this receptor. A Drosophila O-FucT-1 homolog, encoded by O-fut1, catalyzes the O-fucosylation of Notch, a modification essential for Notch signaling and ligand binding. It was recently proposed that O-fut1 acts as a chaperon for Notch in the endoplasmic reticulum and is required for Notch to exit the endoplasmic reticulum. Here, we report that O-fut1 has additional functions in the endocytic transportation of Notch. O-fut1 was indispensable for the constitutive transportation of Notch from the plasma membrane to the early endosome, which we show was independent of the O-fucosyltransferase activity of O-fut1. We also found that O-fut1 promoted the turnover of Notch, which consequently downregulated Notch signaling. O-fut1 formed a stable complex with the extracellular domain of Notch. In addition, O-fut1 protein added to conditioned medium and endocytosed was sufficient to rescue normal Notch transportation to the early endosome in O-fut1 knockdown cells. Thus, an extracellular interaction between Notch and O-fut1 is essential for the normal endocytic transportation of Notch. We propose that O-fut1 is the first example, except for ligands, of a molecule that is required extracellularly for receptor transportation by endocytosis.